ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA DENGAN METODE HAZARD DAN OPERABILITY (HAZOP) PADA CV. XYZ - Sebayang, Albert Ericson; Sukania, I Wayan; Adianto (Jurnal Mitra Teknik Industri, 2023)
CV. XYZ itself has several occupational health and safety standards implemented in its company. The standards applied to workers are the use of Personal Protective Equipment or PPE (Gloves, Shoes and Masks, Eye Protectors, Leg Protectors, Ear Protectors), handling work accidents, handling emergencies, handling work accidents and prohibiting smoking and carrying dangerous equipment items in factory area. The method used to assess the severity of work accidents that occurred at CV. XYZ is the HAZOP method using likelihood and sovereignity indicators which are then calculated using a risk matrix and then classified in the Hazop Worksheet. The results obtained from the analysis tend to be mild to moderate types of accidents caused by careless workers and a lack of signs listed at the factory so that workers often forget to wear personal protective equipment that has been set according to factory standards. Several solutions to reduce work accidents at CV. XYZ includes setting up production equipment, supervising workers, adding K3 signs in the factory area, adding spare PPE in the factory area.